2022
DOI: 10.1002/smj.3474
|View full text |Cite
|
Sign up to set email alerts
|

Does CEO emotion matter? CEO affectivity and corporate social responsibility

Abstract: While prior research has generated meaningful insights into the antecedents of firms' corporate social responsibility (CSR), little attention has been devoted to examining the influence of CEO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The existing literature on disclosure and innovation has mainly examined the moderating role of factors such as corporate characteristics (Wu et al, 2020;Yin et al, 2022) and institutional environment (Guo et al, 2022;Li, Ruan, et al, 2022), while less consideration has been given to CEO characteristics. In fact, it has been noted that CEO characteristics have a significant impact on CSR (Meier & Schier, 2021;Wang, Lin, et al, 2022) and green innovation practices (Quan et al, 2023;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature on disclosure and innovation has mainly examined the moderating role of factors such as corporate characteristics (Wu et al, 2020;Yin et al, 2022) and institutional environment (Guo et al, 2022;Li, Ruan, et al, 2022), while less consideration has been given to CEO characteristics. In fact, it has been noted that CEO characteristics have a significant impact on CSR (Meier & Schier, 2021;Wang, Lin, et al, 2022) and green innovation practices (Quan et al, 2023;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature on disclosure and innovation has mainly examined the moderating role of factors such as corporate characteristics (Wu et al, 2020; Yin et al, 2022) and institutional environment (Guo et al, 2022; Li, Ruan, et al, 2022), while less consideration has been given to CEO characteristics. In fact, it has been noted that CEO characteristics have a significant impact on CSR (Meier & Schier, 2021; Wang, Lin, et al, 2022) and green innovation practices (Quan et al, 2023; Zhou et al, 2021). Hence, this study extends the literature by highlighting the importance of potential moderators that may affect the relationship between corporate EID and green innovation, substantially advancing knowledge about the impact of CEO characteristics on corporate strategic choice and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hometown CEOs often have relationships with local stakeholders and other social roles. CEOs with higher status can attract more attention than their peers, and their influence is often broader and more profound (Wang et al, 2022). Under this consideration, hometown CEOs may acquiesce that they should meet the expectations of all sectors of society and consider the overall interests of their hometowns (Oware and Awunyo-Vitor, 2021).…”
Section: Ceo's Hometown Identity and Corporate Environmental Violationsmentioning
confidence: 99%
“…In previous research, the demographic characteristics of CEOs, such as their gender (McGuinness et al, 2017), marital status (Hegde & Mishra, 2019), and degree (Sun et al, 2021), as well as professional background (Garcia-Sanchez and Martinez-Ferrero, 2019), experience (Al-Shammari et al, 2022), tenure (Chen et al, 2019;Jeong et al, 2021) and multiple positions (Bose et al, 2022), have been extensively and deeply studied. In addition, the deeper characteristics of CEOs, such as their arrogance (Tang et al, 2018), narcissism (Al-Shammari et al, 2019), emotion (Wang et al, 2022), values (Prompeler et. al., 2023, childhood experience (Choi et al, 2023), entrepreneurial spirit , and moral leadership (Tu and Lu, 2016), have also gradually attracted the attention of scholars and have been confirmed to have direct or indirect impacts on CSR.…”
Section: Ceo Characteristics Corporate Environmental Responsibility A...mentioning
confidence: 99%
“…Moreover, CEO succession positively impacts post‐succession CSR, which is enhanced by CEOs' age and weakened by their external origin (Liu, 2020). Positive CEO sentiment increases corporate involvement in social responsibility, while negative CEO emotions decrease a firm's commitment to social responsibility (Wang, Lin, et al, 2022). Using a sample of US firms, the researchers found that firms' CSR performance was significantly higher in the early tenure of the CEO than in the later tenure (Chen et al, 2019).…”
Section: Literature Analysis and Hypothesesmentioning
confidence: 99%